Apparel industry of Bangladesh and customer-based brand equity in developing consumers' purchase decision. (20th April 2023) - Alam, Md. Nur; Masroor, Imtiaz; Chatterjee, Saurav; Hasan, Syed Shamim; Rifat, S.M.; Quadir, Md. Akramul
Brand equity has become an important factor in buying decisions and is increasing the value of a product because it affects customer loyalty and satisfaction. People are more likely to buy or use products from a company if that company has stronger brand equity. With the progressively complex environment in the business sector, the export-oriented apparel industry in Bangladesh is facing extreme challenges. Customer-based brand equity has a positive effect on a company's competitive strategy and helps the company stand out on the market. Understanding the brand equity creation might help in increasing export performance of the apparel industry in Bangladesh. The capacity of brand equity to value creation for consumers and customers alike has generated a burgeoning appeal. This study examined the four factor of brand equity (brand image, brand awareness, perceived quality, and brand association) on consumers' purchasing decision exploring the causality among them. This study is quantitative in nature and a self-administered structured questionnaire was developed to collect data from 203 respondents who purchased from brand shops. Data were analysed using Spearman's ρ correlation and hierarchical regression and found that three of the four developed hypotheses were supported, and one was not supported.